Yours sincerely, giraffe - Iwasa, Megumi, 1958- (Gecko Press, 2016)
When Giraffe decides to write a letter and send it to the other side of the horizon, he finds a penguin pen pal and the two curious animals begin to exchange letters to try to learn more about each other.